-6(h-4)=3(h+9)

Simple and best practice solution for -6(h-4)=3(h+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(h-4)=3(h+9) equation:



-6(h-4)=3(h+9)
We move all terms to the left:
-6(h-4)-(3(h+9))=0
We multiply parentheses
-6h-(3(h+9))+24=0
We calculate terms in parentheses: -(3(h+9)), so:
3(h+9)
We multiply parentheses
3h+27
Back to the equation:
-(3h+27)
We get rid of parentheses
-6h-3h-27+24=0
We add all the numbers together, and all the variables
-9h-3=0
We move all terms containing h to the left, all other terms to the right
-9h=3
h=3/-9
h=-1/3

See similar equations:

| X-(10+10x)=-28 | | 13x+2=17x-2 | | 80°=x+87 | | -10x-5=-8x+10 | | -16=k/8 | | 1/3-t=45 | | 3=p+17 | | 15x-5=70° | | 0.0214=m-0.301 | | –3w−5=–3w−6 | | -8(2-1/48)=2(s-8) | | 1.3b=2.6 | | 20x+5=9x+11 | | –2s=–2s+2 | | 3x-8=4(x+5 | | 8w-28-6w=9w-8-9w | | 16=(2/3)(4)y | | (4y-15)=180 | | b-18=-1 | | -1/10a=-16 | | 2/3x-11=3 | | 7c+4.0=-14.2 | | (2/3)x-11=3 | | 23+4x-39=-11 | | -3x-11=-55 | | -2y+3-3y=18 | | (y-4)/2=8 | | 0.13x5.1=0.633 | | 8)x-3+17=31 | | 38=3w-7 | | -4x-25+2x=-23 | | -5(-2r+6)=5r |

Equations solver categories